College students with social and humanistic consciousness: The case Team-UNA - Barrantes-Elizondo, Lena (2016)
The main objective of Team-UNA outreach project aims at promoting the participation of students in the English Teaching Major as tutors for high schoolers in public institutions in their community. Through this project, the Brunca extension intends to accomplish a social and humanistic university education to future professionals that may satisfy some of the region’s development needs. This experience provides university students with concrete learning tools since they are placed under real educational scenarios. These real-life teaching opportunities are identified as alternative education. Additionally, since students do not get any financial remuneration for teaching these tutorials, it builds a humanistic perspective in students due to the fact that the main goal is to share with their immediate community their academic knowledge and capacity to serve with no other interest more than common good.